DEVELOPMENT AND QUANTITATIVE EVALUATION OF LEADING AND LAGGING METRICS FOR PHA, OP, AND EPR FOR PROCESS SAFETY PERFORMANCE - SHAMIM, MUHAMMAD YASIR (2019)
To face the safety challenges in terms of process disasters, the Occupational Safety and Health Administration (OSHA) of the United States (US) enacted process safety management (PSM) standard having 14 elements in 1992.